FETO-MATERNAL OUTCOMES IN MECONIUM-STAINED LIQUOR IN WOMEN WITH POSTDATE PREGNANCY - PARVEZ, KF; NADIA, . (Biological and Clinical Sciences Research Journal, 2024)
Meconium-stained amniotic fluid (MSAF) during labor is associated with an increased risk of adverse maternal and fetal outcomes, particularly in postdate pregnancies. Prompt recognition and management are crucial to reducing complications. Objective: This study aimed to assess the maternal and fetal outcomes in women with meconium-stained amniotic fluid (MSAF) during postdate pregnancies. Methodology: A cross-sectional study was conducted at the Department of Obstetrics and Gynecology from May 2024 to November 2024, with 118 women aged 18 to 40 years. The inclusion criteria were women with postdate pregnancies (gestational age > 40 weeks), singleton cephalic presentations, and the presence of meconium-stained amniotic fluid during labor. Fetal and maternal outcomes were examined. Results: Perinatal asphyxia occurred in 11.0%, NICU admission in 19.5%, meconium aspiration syndrome in 6.8%, neonatal sepsis in 8.5%, and neonatal death in 3.4%. Maternal outcomes included cesarean section in 26.3%, puerperal sepsis in 16.1%, and chorioamnionitis in 4.2%. These outcomes suggest a higher incidence of complications in both mothers and neonates with MSAF. Conclusion: This study highlights the increased risk of perinatal asphyxia, NICU admission, meconium aspiration syndrome, neonatal sepsis, and early neonatal death in neonates with meconium-stained amniotic fluid. Maternal outcomes also show higher rates of cesarean sections and puerperal sepsis, emphasizing the need for careful monitoring and intervention.